A didactic sequence from a gamification application for reading the status of children and adolescents: an active methodology (Research, Society and Development, 2020)
Information and Communication Technologies - ICTs have become important allies in teaching and learning and, in order to implement them, schools and teachers need to review their practices and look at their students as individual beings, perceiving them as understanding the languages ​​of games, because playing is in your daily life. However, for best results, such tools cannot be run mechanically. He needs to receive from the teacher the interference of an active methodology to enrich him. Thinking about the Brazilian school today leads Education scholars to the following question: can a game be a student-centered work proposal for a collaborative posture and perception of its otherness? Question that leads to the objective of building this didactic sequence on the perspective of a methodological approach proposed by Dolz, Noverraz and Schnewly, with the purpose of describing actions that can enhance the elementary school students from the 5th to the 9th year for making critical decisions and expand your perception of collective social actions. Through a gamification application, the quiz, based on the National Common Curricular Base, proposes a qualitative study, with the theme: status of children and adolescents, guided by basic authors: Deterding, Burden, among other theorists. Thus, it is believed that the didactic sequence can be considered a contribution proposal for the school to evolve and motivate its students more, in view of its potential to arouse interest and participation of students, making them more proactive, responsive, developing their multiliteracies.